1980
DOI: 10.2330/joralbiosci1965.22.30
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure, ultracytochemistry and histochemistry of the submandibular gland of the field mouse. Apodemus argenteus Temminck

Abstract: Ultrastructure, ultracytochemistry and histochemistry of the submandibular gland of the fi eld mouse. Apodemus argenteus Temminck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…TAMARIN and SREEBNY (1965) reported that dark and basal cells were distinguishable in the rat submandibular gland, and WILBORN and SHACKLEFORD (1969) demonstrated that clear, dark, and basal I and II cells were distinguishable in SD cells in the opossum. The dark cells found in the Japanese wood mouse were similar in cytological appearances to the dark cells of Apodemus aygenteus TEMMINCK (ODAJIMA, 1980). The vesicles observed in the apical region of the dark SD cells were similar in appearance to those found by RUTBERG (1961) in the SD cells of the mouse submandibular gland.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…TAMARIN and SREEBNY (1965) reported that dark and basal cells were distinguishable in the rat submandibular gland, and WILBORN and SHACKLEFORD (1969) demonstrated that clear, dark, and basal I and II cells were distinguishable in SD cells in the opossum. The dark cells found in the Japanese wood mouse were similar in cytological appearances to the dark cells of Apodemus aygenteus TEMMINCK (ODAJIMA, 1980). The vesicles observed in the apical region of the dark SD cells were similar in appearance to those found by RUTBERG (1961) in the SD cells of the mouse submandibular gland.…”
Section: Discussionsupporting
confidence: 65%
“…In the Japanese wood mouse, the average diameter of the male CGTs was significantly larger than that of the female, although in Apodemus argenteus TEMMINCK which is of the same genus, sex differences in the diameter of CGTs were not observed (ODAJIMA, 1980). There are some variations in the sexual dimorphism of the CGTs within the same genus.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations